Association between encephalopathy and clinical outcomes of COVID-19: Findings from the Philippine CORONA Study - V.M.M. Anlacan; F.G.C. Gabriel; R.D.G. Jamora; E.Q. Villanueva III; M.C.C. Sy; M.H.L. Lee Yu; A.I. Espiritu (Neurología (English Edition))
Introduction: This study aimed to determine whether encephalopathy is associated with such COVID-19 outcomes as disease severity, mortality, respiratory failure, intensive care unit (ICU) admission, duration of ventilator dependence, and length of ICU and hospital stay. Methods: We performed a subgroup analysis comparing outcomes in patients with and without encephalopathy, based on data from a nationwide retrospective cohort study among adult patients hospitalized with COVID-19 at 37 hospital sites in the Philippines. The patient outcomes included for analysis were disease severity, mortality, respiratory failure, ICU admission, duration of ventilator dependence, and length of ICU and hospital stay. Results: Of a total of 10 881 COVID-19 admissions, 622 patients had encephalopathy. The adjusted hazard ratios (aHR) for mortality among mild and severe cases were 9.26 and 1.63 times greater (P < .001), respectively, in the encephalopathy group compared to the no-encephalopathy group. Encephalopathy was associated with increased risk of severe COVID-19 (adjusted odds ratio [aOR]: 7.95; P < .001), respiratory failure (aHR: 5.40; P < .001), longer hospital stays (aOR: 1.36; P < .001), and admission to the ICU (aOR: 4.26; P < .001). We found no sufficient evidence that encephalopathy was associated with length of ICU stay (aOR: 1.11; P = .522) or duration of ventilator dependence (aOR: 0.88; P = .428). Conclusions: Encephalopathy was associated with COVID-19 severity, mortality, respiratory failure, ICU admission, and longer hospital stays. Resumen: Introducción: Nuestro estudio tuvo como objetivo determinar si la encefalopatía estaba asociada con los resultados de COVID-19, como la gravedad de la enfermedad, la mortalidad, la insuficiencia respiratoria, el ingreso a la unidad de cuidados intensivos (UCI) y la duración de la dependencia del ventilador, la estancia en la UCI y en el hospital. Métodos: Realizamos un análisis de subgrupos comparando los resultados de los pacientes con encefalopatía frente a los pacientes sin encefalopatía, basado en datos de un estudio de cohorte retrospectivo a nivel nacional entre pacientes adultos hospitalizados con COVID-19 en 37 hospitales en Filipinas. Los resultados del paciente incluidos para el análisis fueron la gravedad de la enfermedad, la mortalidad, la insuficiencia respiratoria, el ingreso a la UCI y la duración de la dependencia del ventilador, la estancia en la UCI y en el hospital. Resultados: De las 10.881 admisiones totales por COVID-19, 622 pacientes tenían encefalopatía. Las razones de riesgo ajustadas (aHR) para la mortalidad entre casos leves y graves fueron mayores en 9,26 y en 1,63 (p < 0,001), respectivamente, en el grupo de encefalopatía en comparación con el grupo sin encefalopatía. La encefalopatía se asoció con un mayor riesgo de tener COVID-19 grave (razón de posibilidades ajustada [aOR] 7,95, p < 0,001), insuficiencia respiratoria (aHR 5,40, p < 0,001), estancia hospitalaria más larga (aOR 1,36, p < 0,001) e ingreso a la UCI (aOR 4,26, p < 0,001). No encontramos suficiente evidencia de que la encefalopatía estuviera asociada con la duración del ingreso a la UCI (aOR 1,11, p = 0,522) y la duración de la dependencia del ventilador (aOR 0,88, p = 0,428). Conclusiones: La encefalopatía estuvo asociada con la gravedad de la COVID-19, la mortalidad, la insuficiencia respiratoria, el ingreso a la UCI y una estancia hospitalaria más prolongada.